2019
DOI: 10.1111/1471-0528.16024
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome in 7‐year‐old children is not affected by exercise during pregnancy: follow up of a multicentre randomised controlled trial

Abstract: Objective To investigate whether regular moderate intensity exercise during pregnancy had adverse effect on neurodevelopment of offspring at 7 years of age. Design Follow up of a multicentre randomised controlled trial. Setting St Olavs Hospital, Trondheim University Hospital and Stavanger University Hospital, Norway (2007–09). Population Women randomised to follow a 12‐week structured exercise protocol or standard antenatal care during pregnancy. Methods At 7 years of age, neurodevelopmental outcome was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Few studies have examined the association between maternal MVPA in pregnancy and child motor development. Of the existing studies, measurement of developmental skills varies greatly, including cognitive, language, motor, and intelligence domains, making it difficult to compare findings [ 17 , 18 , 19 , 29 ]. In one observational cohort study, most similar to our study, and including 528 pregnant women, maternal leisure time physical activity was self-reported in each trimester and development was measured using the Bayley Scales of Infant and Toddler Development in children at 1- and 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have examined the association between maternal MVPA in pregnancy and child motor development. Of the existing studies, measurement of developmental skills varies greatly, including cognitive, language, motor, and intelligence domains, making it difficult to compare findings [ 17 , 18 , 19 , 29 ]. In one observational cohort study, most similar to our study, and including 528 pregnant women, maternal leisure time physical activity was self-reported in each trimester and development was measured using the Bayley Scales of Infant and Toddler Development in children at 1- and 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This study then compared the developmental scores of children (intervention: n = 164, control: n = 115) at 7 years of age using the ‘Five-to-Fifteen’ motor development questionnaire. No differences were found in fine or gross motor score domains in children born to mothers in the intervention compared to the control groups [ 18 ]. Another randomized controlled trial which also included one in-person and two at-home 45 min sessions per week but limited to aerobic exercise only (intervention: n = 188, control n = 148), measured development using the Bayley Scales of Infant and Toddler Development in children at 18 months old and also found no significant differences in overall motor development scores between intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy outcome and newborn data were registered at time of delivery [ 25 ]. The children were clinically assessed at 18 months of age [ 10 ] and by parent-report at 7 years of age [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that exercise in pregnancy is safe [ 25 ], and does not have adverse effects on the child’s neurodevelopment at 18 months [ 10 ] or 7 years of age [ 11 ]. In the current study, our primary aim was to investigate whether an exercise intervention during pregnancy affected BMI and PA of the children at 7 years of age.…”
Section: Introductionmentioning
confidence: 99%